Schriftträger - Textträger: zur materiellen Präsenz des Geschriebenen in frühen Gesellschaften - Kehnel, Annette; Panagiotopoulos, Diamantis (Materiale Textkulturen, 2014)
This volume seeks to explore new interpretive approaches to textual sources from past cultures that emphasize their materiality and praxeology. The focus of inquiry is on the relationship between the text and its material carriers and on the influence of material forms on the creation, presence, and reception of what is written.